THE FACTORS THAT MOST INFLUENCE THE ATTRACTION OF THE MOVEMENT AT ST PAUL'S CATHOLIC MIDDLE SCHOOL, PALANGKA RAYA - Meilano Saputri; Samuel Layang (Jurusan Pendidikan Teknologi Dan Kejuruan, 2023)
Transportation is a basic need of an area that is used as an effort to improve the welfare of its population. Transportation planning is absolutely necessary to find the most efficient solution of the interaction of movement. Movement begins with the rise and pull of movement (Trip Generation). The education area is one of the land uses that generates mass movements and has a large size. Therefore, research was conducted on the pull of movement in the educational area at St. Paul Catholic Junior High School Palangka Raya using multiple linear regression analysis. That way it can be known the factors that most affect the pull of movement as well as the best model that can be made. The study was carried out for 6 working days, namely on Monday-Saturday at peak hours. The collected vehicle data is then converted into passenger car units. The variables used are the pull of vehicle movement (Y), land area (X1), building area (X2), number of classes (X3), number of students (X4) and number of teachers and employees (X5). Analysis using SPSS software version 26. Various data tests were carried out to obtain appropriate results, the results of the analysis and tests that have been carried out concluded the best model of total travel attraction (junior high school / hour), namely Y = -2645.194 + 4.194X4 + 6.452X5 where X4 is the number of students and X5 is the number of teachers and employees. Based on the results of the analysis, it is concluded that Factors whomost influence the pull of the movement are the number of students and the number of teachers and employees.